Awareness of acute myeloid leukaemia risk induced by diagnosis of a myelodysplastic syndrome. (July 2016) - Ousseine, Youssoufa M.; Butow, Phyllis N.; Julian-Reynier, Claire; Dring, Rebecca; Festy, Patrick; Fenaux, Pierre; Vey, Norbert; Mancini, Julien
Highlights: One in three MDS patient (33.2%) were not aware of their risk of developing AML. Awareness of AML risk decreased with age and lower-risk MDS treatment. Awareness of AML risk might increase the rate of clinical trial participation. Abstract: Myelodysplastic syndromes (MDS) can evolve to acute myeloid leukaemia (AML) in approximately 30% of cases. Knowing their AML risk is important for patients because it might impact adherence to care and psychological health. The aim of this study was to evaluate the awareness of AML risk among MDS patients and to study the factors associated with this awareness. A self-administered questionnaire was mailed to all members of French and Australian patients' national MDS associations. Data of 301 patients were analysed. Patients were satisfied with the information they had received, but 33.2% did not know that they had an increased risk of developing AML. Younger age, higher-risk MDS treatment, preferences for health-related information and satisfaction with information provided about treatment were the factors independently associated with awareness of AML risk. Compared to unaware patients, patients knowing their risk were more likely to participate in a hypothetical clinical trial (83.0% vs 72.4%, p = 0.043). More efforts are needed to provide more systematic information about AML risk to patients wishing to know it. More research is needed to study if increasing awareness can lead to more active engagement of MDS patients in their care and can increase the rate of clinical trial participation.